Giving behaviour: Who donates cash WAQF? - Syadiyah Abdul Shukor; Intan Fatimah Anwar; Hisham Sabri; Sumaiyah Abd Aziz; Avylin Roziana Mohd Ariffin (Malaysian Consumer and Family Economics Association, 2024)
Indexed by Scopus